Application of Fourier Transform Infrared Spectroscopy and X-Ray Diffraction in the Characterization of Bamboo Stalks - Onimi Ometere Ashama; Tina Ishioma Francis-Akilaki (Greenation International Journal of Engineering Science, 2026)
Bamboo stalks have recently attracted increasing attention as sustainable agricultural by-products because of their rapid growth cycle, self-regeneration ability, and low maintenance requirements. Bamboo is widely distributed across tropical and subtropical regions of Nigeria, with Oxytenanthera abyssinica being one of the most dominant species. In spite of its extensive use in construction and craft applications, the material potential of bamboo stalks for engineered wood products remains underexplored. This study investigates the suitability of bamboo stalks as an eco-friendly precursor for particleboard production using Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD) methods. FTIR analysis result revealed that characteristic absorption bands associated with cellulose, hemicellulose, and lignin, with prominent peaks observed at 1737 cm⁻¹, 1511 cm⁻¹, and 1379 cm⁻¹. Also, XRD analysis result showed distinct diffraction maxima at 2θ angles of approximately 15° and 22°, indicative of a high degree of cellulose crystallinity. Chemical composition analysis established that the bamboo biomass contained 52.61% cellulose, 19.16% hemicellulose, and 24.27% lignin, with negligible amounts of extractives (2.21%) and ash (1.75%). The combined FTIR and XRD results prove that bamboo stalks possess favourable chemical and structural properties, supporting their potential application as sustainable raw materials for particleboard manufacturing.